Pengaruh Analisis Jabatan dan Pengembangan Karir terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Dinas Pengendalian Penduduk dan Keluarga Berencana (DPPKB) Kabupaten Tanjung Jabung Timur - Nurdianto, Nurdanto; Suryani, Arna; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to find out a description of job analysis, career development, job satisfaction and employee performance at the Population Control and Family Planning Service (DPPKB) of East Tanjung Jabung Regency as well as to find out and analyze the influence of job analysis and career development on employee performance through job satisfaction at the Control Service Population and Family Planning (DPPKB) East Tanjung Jabung Regency. This type of research uses descriptive verification research. This research uses the PLS analysis method.  Based on the results of the questionnaire regarding job analysis, it is 2,876 in the quite good category. Then, the description of the career development variable shows that the career development of employees at the Population Control and Family Planning Service (DPPKB) of East Tanjung Jabung Regency is quite good with a score of 1653. Furthermore, the description of the job satisfaction variable shows that the job satisfaction score is 1849 in the quite high category. Meanwhile, the description of employee performance variables shows that the score is 2850 in the quite high category. Based on the research results, job analysis and career development have a positive and significant effect on job satisfaction, job analysis, career development and job satisfaction have a positive and significant effect on employee performance, position analysis and career development have a positive and significant effect on employee performance, mediated by job satisfaction in Tanjung East Jabung.